Flavonoides de Ephera americana (pinco pinco), acción biológica sobre el sistema inmunológico (IgE) - Bonilla Rivera, Pablo (2001)
In the present investigation we have developed a phytochemical study and detennined the biological activity of the aerial parts of a vegetal Peruvian species named Ephedra americana Known as "pinco-pinco". It grows in the highlands of Cusco-Perú, in the province of Calca, approximately at 3500 m.o.s.l. The powder of the sample was used to for the phytochemical screening in wich we identified the presence of alkaloids, phenolic compounds, flavonoids types, tannins, glicosydes, etc. By means of a solubility screening test, it was detennined that the secondary metabolites were moderately and highly polar.This was pruved by means of Thin Layer Chromatograpy. Also, a separation of the phenolic compouunds by Flash Column Chromatograpy has been performed, obtaining many fractions. These were purified by means of Preparative Scale Chromatograpy using various solvent systems and five flavonoids with accepted antioxidant activity were structurally elucidated: hesperidin; chrisyn; 3',4' ,5,7-tetrahidroxi-6,8-di R flavone; 3' ,5,7-trihidroxi-4' ,6-dimetoxi flavonol and 4'hidroxi- 5,7-dimetoxi flavanone. In the ethanolic extract it has been detenninated the inmunostimulant activity, the antioxidant effect, toxic action by Artemia salina, antiulcer activity, action on the intestinal motility, anti-inflammatory activity, toxicity and antimicrobial activity.